STI system in universities of Vietnam - Truong, Dao Thanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Science, Technology and Innovation (STI) has become an important means and goal of countries for national development and international integration. The STI system not only serves as a link of different stakeholders, i.e State - Enterprise - Research Institute - University not only to make achievements in socio-economic development, but also to enhance the internal capacity of each element. In the STI system, universities and colleges play an important role because they are not just considered as a provider of high quality scientific and technological (S&T) manpower but also a nursery to incubate scientific ideas, research and development achievements before putting them into production. Through a case study of four universities: Vietnam National University, National University of Ho Chi Minh City, Hanoi University of S&T and University of Thai Nguyen, the author of this paper described and assessed the status of STI activities in those universities to understand the present capacity and the role of universities in aligning their research - training - production functions in the STI system. Code: 15101501